Gambierol and n-alkanols inhibit Shaker Kv channel via distinct binding sites outside the K+ pore. (15th September 2016) - Martínez-Morales, Evelyn; Kopljar, Ivan; Rainier, Jon D.; Tytgat, Jan; Snyders, Dirk J.; Labro, Alain J.
Abstract: The marine polycyclic-ether toxin gambierol and 1-butanol (n-alkanol) inhibit Shaker -type Kv channels by interfering with the gating machinery. Competition experiments indicated that both compounds do not share an overlapping binding site but gambierol is able to affect 1-butanol affinity for Shaker through an allosteric effect. Furthermore, the Shaker -P475A mutant, which inverses 1-butanol effect, is inhibited by gambierol with nM affinity. Thus, gambierol and 1-butanol inhibit Shaker -type Kv channels via distinct parts of the gating machinery. Highlights: The marine toxin gambierol and 1-butanol do not compete as inhibitors of the Shaker Kv channel. Gambierol and 1-butanol are gating modifiers that induce channel inhibition by stabilizing a non-conducting conformation. The Shaker pore mutant P475A remains sensitive to gambierol displaying nanomolar affinity. Pore mutation T469V reduces Shaker 's sensitivity to gambierol but does not affect the response to 1-butanol.